Mission and Colonialism: Ludwig Harms’ and the Hermannsburg Mission’s Romantic Approach - Reller, Jobst (Communio viatorum, 2025)
The original vision of the founder of the Hermannsburg mission, Pastor Ludwig Harms (1808-1865) was deeply rooted in the period of romantic revival in Germany in the early 19th century. Whole congregations of missionaries and colonists should be sent overseas together. Although critical of colonialism, the mission and its settlers became later part of a colonial and even racist society in South Africa. Did the vision influence the social concept six generations later in the former mission field? Did it slow down the process of indigenization, lock up in racist concepts like "apartheid"? The essay provides many hints in that direction and exposes a specific variant of the interaction of migration, colonialism and mission.